Early Adolescents’ Social Achievement Goals and Perceived Relational Support: Their Additive and Interactive Effects on Social Behavior - Shin, Huiyoung (Frontiers in Psychology, 2021)
The current study examined the additive and interactive effects of early adolescents’ social achievement goals and perceived relational support from teachers and peers on their social behavior. Adolescents’ social achievement goals (i.e., social development, social demonstration-approach, and social demonstration-avoidance), perceived relational support from teachers and peers, and social behavior (i.e., overt and relational aggression, prosocial behavior, and anxious solitary behavior) were assessed in a sample of fifth and sixth graders (Mage =12.5; N = 677) nested within 26 classrooms. Multilevel modeling results indicated that social goals and relational support from teachers and peers made additive contributions to adolescents’ social behavior. Results also indicated the evidence of interactive effects, such that relational support from teachers was negatively associated with overt and relational aggression primarily among adolescents who had high social demonstration-approach goals. Findings underscore the need to consider adolescents’ social goals in conjunction with their perceived relational support for educators and practitioners.